Features of the oxidation of multiwalled carbon nanotubes - Savilov, S. V.; Ivanov, A. S.; Chernyak, S. A.; Kirikova, M. N.; Ni, J.; Lunin, V. V. (Russian Journal of Physical Chemistry A, 2015)
Features of the functionalization of multiwalled carbon nanotubes (MWCNTs) with a conical (Ni precursor) and cylindrical (Fe precursor) arrangement of graphene layers using various oxidizing agents are studied. The initial diameter of pyrolytically prepared tubes varies from 20 to 80 nm with a maximum at 40–45 nm and from 10 to 30 nm with a maximum at 18 nm in the first and second cases, respectively. Oxidative modification of the MWCNT surfaces is conducted using HNO 3 and H 2 O 2 with ultrasound activation, ozonation in a glow discharge plasma of oxygen, and treatment with liquid ozone. Thermal and elemental analyses and IR spectroscopy show that the highest content of functional groups is achieved in the samples treated with nitric acid, where the conical MWCNTs are subject to surface functionalization. It is concluded that in order to achieve a similar result, cylindrical tubes must be treated with liquid ozone.